Modified Sprint Interval Intervention Produces Lower Inter-Subject Variability in Physiological and Performance Adaptations Across Collegiate Soccer Players. - Peng, Qian; Zhang, Zhen; Gao, Liang; Zhang, Hui; Liu, Yu (Journal of Sports Science & Medicine, 2025)
This experiment investigated the uniformity of the adaptations to high-intensity-interval training (HIIT) prescribed using anaerobic speed reserve (ASRHIIT [The difference between maximal sprint speed and maximal aerobic speed]), maximal aerobic speed (MASHIIT), and a load-matched sprint interval training (SIT) in male collegiate soccer players. Thirty collegiate male soccer players with 4-6 years of training experience (age = 21.6 ± 4.8 years; height = 182.4 ± 4.4 cm; body mass = 84.1 ± 3.3 kg; body fat = 13.1 ± 3.6%) were randomized to three experimental groups performing either ASRHIIT or MASHIIT (4 sets of 4 - 7 repetitions of 30-sec running at Δ%30ASR (MAS + 0.3xASR) or 130% MAS, from the 1st to the 7th session) or a load-matched SIT. Participants underwent a series of lab- and field-based tests to evaluate measures of cardiorespiratory fitness (i.e., maximal oxygen uptake, cardiac hemodynamics and ventilatory threshold), anaerobic power (i.e., peak and average power), and bio-motor abilities (i.e., maximal sprint speed, change of direction, and jumping ability). Homogeneity of the adaptive changes was investigated by comparing residuals in individual changes and calculating the coefficient of variation in mean group changes. All three interventions adequately stimulated the adaptive mechanisms involved in the enhancement of the qualities mentioned above (p < 0.05). Linear sprint speed improved solely in response to SIT (p = 0.001). Moreover, load-matched SIT led to significantly greater enhancements in measures of bio-motor abilities compared to ASRHIIT and MASHIIT (p < 0.05). ASRHIIT and SIT resulted in lower intersubject variability in adaptive responses in cardiorespiratory fitness measures (p < 0.05). Optimizing homeostatic stress through load-matched SIT leads to more homogenous adaptations across individuals and significantly greater adaptations in bio-motor abilities than the other prescription approaches. It's worth noting that genetic variability, motivation, diet, sleep quality, and psychological factors can influence inter-individual responses. These aspects were not accounted for in the current experiment and represent potential limitations.